MEANINGFUL EDUCATION WITH EFFORTS TO CREATE SYNERGY BETWEEN ETHICS, LOGIC, AND AESTHETICS IN FORMING STUDENTS WITH CHARACTER - Susdarwono, Endro Tri (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2022)
This study aims to provide a description regarding meaningful education with efforts to create synergy between ethics, logic, and aesthetics in forming students with character. In this study, ethics, logic and aesthetics are related to the formation of student character. Next to our ideals to create a new education system which results in humans who have harmony between reason and morality, ratio and morality, still come true, that education in our country up to right now, still walking on the tracks of secular education. Namely an educational system that is intellectualistic only and the results do not cause satisfaction, for the educated self, even more so for the demands of the community that we want to build right now. Today's modern education, it is merely an education that is adapted to the demands of science and mere technical needs. The result is that we also experience an educational form where the subjects are too intellectualistic, and his teaching is also very verbalistic. So that way, moral education seems to be ruled out with a lack of meaning. This paper discusses how synergy of ethics, logic and aesthetics in education as a balance of Intellectualism in facing the digital age, so that it can be a material for further thinking to solve this acute national problem.